Test Research and Strength Calulation on the spalling damage of surface hardened Gear wheels - Huang Qiubo; et al. (Jixie chuandong)
Test researches were made on thesimulate spalling damage of the tooth surfacesof 30 pairs of steel- rollers with 4 differentdepth of carburired layer. Based on these researches and the viewpoint of fatique, that isto consider the stress.amplitude and the characteristics of stress cycle as well as the reasonable matching between the contact stressfield and the’matetial strength field, this article further clarifies the stress which causesthe fatique-spalling, and derives thestrength conditional foumula used to preventthe spalling damage of the surface hardenedgears, according to the strength and the hardness of the ordinary materials after being surface hardened and to the approximate ralations among the relative strength limits.